Sound Check: Bylaws, Busking and the Local Government Act 2002 - Wright, Fiona (Victoria University of Wellington Law Review, 2005)
This article examines the law-making powers of local authorities under the Local Government Act 2002. It argues that there are insufficient checks and balances on local government law-making, which may lead to local government powers being misused. It also criticises the Act's processes of bylaw enactment and review, arguing that they may encourage local authorities to abandon bylaws in favour of the new power of general competence, under which local authorities can operate beyond the relative safety of many existing checks and balances.